2021
DOI: 10.2196/27392
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of User-Oriented Information Services on the Websites of Large Hospitals in China and the United States: Cross-sectional Study

Abstract: Background Many people use the internet to access health care information to support health care decisions, and hospital websites can be the first point of contact to provide health care information services for consumers. However, little is known about the current information services provided by the websites of large Chinese hospitals. Objective The aim of this study is to evaluate and compare the information services of the websites of large hospital… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Internet usage statistics have revealed that the global penetration rate has reached 62.5% with impressive growth in recent years. More than 5 billion people across the globe have internet access (Zhong et al, 2021). The effect of internet dependency is very prominent in the present business environment.…”
Section: Introductionmentioning
confidence: 99%
“…Internet usage statistics have revealed that the global penetration rate has reached 62.5% with impressive growth in recent years. More than 5 billion people across the globe have internet access (Zhong et al, 2021). The effect of internet dependency is very prominent in the present business environment.…”
Section: Introductionmentioning
confidence: 99%